Riverbed Processes and Stability of the Neman River Course (within the Republic of Belarus) - T. A. Melezh (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2022)
The article provides an assessment of the stability of the Neman riverbed. Author has developed a classification of the Neman River course based on the evaluation of its stability and coastal erosion risk. It has been established that presently the nature of riverbed processes in the Neman Valley is heterogeneous in various sections and even in small segments. On base of obtained results, the author has identified the following segments: Stolbtsovskiy, Lyubchanskiy, Mostovskiy, Grodno, and Sredne-Neman.